2022
DOI: 10.1111/nmo.14390
|View full text |Cite
|
Sign up to set email alerts
|

Fecal luminal factors from patients with irritable bowel syndrome induce distinct gene expression of colonoids

Abstract: Background: Alteration of the host-microbiota cross talk at the intestinal barrier may participate in the pathophysiology of irritable bowel syndrome (IBS). Therefore, we aimed to determine effects of fecal luminal factors from IBS patients on the colonic epithelium using colonoids.Methods: Colon-derived organoid monolayers, colonoids, generated from a healthy subject, underwent stimulation with fecal supernatants from healthy subjects and IBS patients with predominant diarrhea, phosphate-buffered saline (PBS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…Thus, this experimental set-up did not allow for TNF to be used as a positive control stimulus or in TEER measurements. In further support of the findings in this report, our group have recently demonstrated that monolayers of healthy-derived colonoids, comprising a multicellular phenotype, also express a distinct gene profile when stimulated with fecal supernatants from IBS patients [ 21 ]. Taken together, both studies provide a proof of concept that fecal supernatants constitute a proxy for disease-specific metabolite composition and alter the gene expression profiles of intestinal cell lines.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Thus, this experimental set-up did not allow for TNF to be used as a positive control stimulus or in TEER measurements. In further support of the findings in this report, our group have recently demonstrated that monolayers of healthy-derived colonoids, comprising a multicellular phenotype, also express a distinct gene profile when stimulated with fecal supernatants from IBS patients [ 21 ]. Taken together, both studies provide a proof of concept that fecal supernatants constitute a proxy for disease-specific metabolite composition and alter the gene expression profiles of intestinal cell lines.…”
Section: Discussionsupporting
confidence: 79%
“…The use of colon organoids derived from CC and UC patients for studying disease mechanisms and developing individualized therapy strategies has evolved during recent years [ 17 , 18 , 19 , 20 ]. However, studies that investigate the effects of the microbiota on human-derived intestinal organoids are limited [ 21 , 22 , 23 ], and it needs to be determined if external stimuli, such as components and metabolites found in the lumen, are able to induce disease specific phenotypes in organoids derived from healthy human biopsies.…”
Section: Introductionmentioning
confidence: 99%
“…All patients were well‐characterized and presented with moderate to severe symptoms (IBS Severity Scoring System (IBS‐SSS) 36 ≥ 175) 35 . Initially patients classified as IBS‐D (predominantly presenting with watery stools (scores of 6 and 7) according to the Bristol Stool Form (BSF) scale 33 ) were selected from a previous study to increase the group size 37 . However, the limited fecal sample availability of this IBS subtype in the placebo group resulted in the addition of a small group of IBS‐M patients with high severity of symptoms, defined by IBS‐SSS total score ≥ 175.…”
Section: Methodsmentioning
confidence: 99%
“…according to the Bristol Stool Form (BSF) scale 33 ) were selected from a previous study to increase the group size. 37 However, the limited fecal sample availability of this IBS subtype in the placebo group resulted in the addition of a small group of IBS-M patients with high severity of symptoms, defined by IBS-SSS total score ≥ 175. These patients were randomly selected among those reporting an IBS-D like profile at the time of sampling.…”
Section: Key Pointsmentioning
confidence: 99%
“…Several studies have analyzed the response of organoids to fecal supernatants derived from patients with various GI conditions. Treatment of healthy colonoid monolayers with IBS fecal supernatants increased gene expression of immune regulatory, proinflammatory cytokines, and epithelial junctional complexes while decreasing TLR5 expression [92]. Arnauts et al [93] attempted to determine if epithelial cell defects or the microbiota are responsible for barrier dysfunction in UC.…”
Section: Epithelial Cell-microbial Interactionsmentioning
confidence: 99%